Hierarchical clustering for multiple‐crystal macromolecular crystallography experiments: the ccCluster program. Issue 6 (29th November 2017) - Santoni, Gianluca; Zander, Ulrich; Mueller-Dieckmann, Christoph; Leonard, Gordon; Popov, Alexander
Abstract : The ccCluster program provides an easy‐to‐use interface to perform hierarchical cluster analysis on protein diffraction datasets. Abstract : This article describes ccCluster, a software providing an intuitive graphical user interface (GUI) and multiple functions to perform hierarchical cluster analysis on multiple crystallographic datasets. The program makes it easier for users to choose, in the case of multi‐crystal data collection, those datasets that will be merged together to give good final statistics. It provides a simple GUI to analyse the dendrogram and various options for automated clustering and data merging.